(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Stress and Depression are major problems of futuregenerations heading high today. In Most of the organization people aresuffering from this problem. The Present study is an effort to know therelationship of self efficiacy with depression so that it can be further usedto control the impact of depression on the individuals. In this study theresearcher examined the level of depression in relation to self-efficacy. Thefindings further revealed that mild, moderate and severe depression arenegatively related with self-efficacy of an individual. This study can befurther useful to researchers, psychologists, counselors etc.